PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN NASABAH PADA PT.BANK SUMUT CABANG PERCUT SEI TUAN KABUPATEN DELI SERDANG - Tasya Ivana; Erlyanti Erlyanti; Dewi Sundari Tanjung (Fakultas Agama Islam Universitas Al Washliyah, 2025)
This research aims to determine whether service quality has a significant positive effect on customer satisfaction at PT. Bank Sumut Percut Sei Tuan Branch, Deli Serdang Regency, and to determine whether product quality has a significant positive effect on employee performance regarding customer satisfaction at PT. Bank Sumut Percut Sei Tuan Branch, Deli Serdang Regency.The population in this study consists of customers of PT. Bank Sumut Branch Percut Sei Tuan, Deli Serdang Regency. According to Roscoe's theory, the sample in this study amounts to 80 respondents, which is considered adequate and sufficient for this research.The type of research is quantitative research, which is a research method based on positivist philosophy, used to study a specific population or sample.Using multiple linear regression statistical analysis techniques.Thus, the results obtained from this research were obtainedThe quality of service partially has a positive and significant effect on customer satisfaction.This is indicated by the value that t-count X1 (8.151) > t-table (1.98) and p-value (0.000) <0.05,The quality of the product partially has a significant effect on customer satisfaction.This is indicated by the t-statistic value X2 (3.592) > t-table (1.98) and p-value (0.001) <0.05. This is indicated by the t-count value X2 (3.592) > t-table (1.98) and p-value (0.001) <0.05.